An Intuitive, Affordances Oriented Telemanipulation Framework for a Dual Robot Arm Hand System: On the Execution of Bimanual Tasks - Gorjup, Gal; Dwivedi, Anany; Elangovan, Nathan; Liarokapis, Minas (IEEE International Conference on Intelligent Robots and Systems, 2019)
The concept of teleoperation has been studied since the advent of robotics and has found use in a wide range of applications, including exploration of remote or dangerous environments (e.g., space missions, disaster management), telepresence based time optimisation (e.g., remote surgery) and robot learning. While a significant amount of research has been invested into the field, intricate manipulation tasks still remain challenging from the user perspective due to control complexity. In this paper, we propose an intuitive, affordances oriented telemanipulation framework for a dual robot arm hand system. An object recognition module is utilised to extract scene information and provide grasping and manipulation assistance to the user, simplifying the control of adaptive, multi-fingered hands through a commercial Virtual Reality (VR) interface. The system's performance was experimentally validated in a remote operation setting, where the user successfully performed a set of bimanual manipulation tasks.
Created from Fastlane, Scopus look-up